Long-term effects of insulin therapy, islet transplantation, and pancreas transplantation in the prevention of glomerular changes in kidneys of alloxan-induced diabetic rats - Spadella, César Tadeu [UNESP]; Lerco, Mauro Masson [UNESP]; Machado, JLM; Macedo, Célia Sperandeo [UNESP] (Elsevier B.V., 2005)
Groups of inbred alloxan-induced diabetic rats were treated with insulin (I), islets (IT), or pancreas transplantation (PT). Nondiabetic (N) and untreated diabetic (D) control groups were concurrently included. Each group was divided into five subgroups of 10 rats and killed after follow-up of 1, 3, 6, 9, and 12 months. Clinical and laboratory parameters were recorded, and kidney ultrastructural and morphometric analyses performed in each 12-month subgroup, namely glomerular basement membrane (GM) thickening, podocyte number, and number/extension of slit diaphragms (S). Rats from the I group showed poor metabolic control of diabetes compared with N group control rats. However, successfully transplanted rats (IT and PT) had complete restoration to normal levels for all metabolic parameters. GM thickening was significantly higher in diabetic compared with control rats. In contrast, the numbers of podocytes and slits as well as slit extensions were significantly decreased. Insulin therapy did not prevent any alterations upon comparison of diabetic vs control rats. Despite good metabolic control in IT rats, the degree of kidney lesion control never compared with that achieved in PT rats. In this group all glomerular changes were similar to the age-dependent lesions observed in control rats. We conclude that either IT or PT may be a good option for diabetes treatment, although pancreas transplantation seems to be the most effective treatment to control chronic complications.